Noise in the Workplace: Assessment of Occupational Hearing Loss Risk Based on Audiometric Changes - Beha, Admira; Jović, Ozren; Huremović, Alma (Technium Social Sciences Journal, 2026)
Noise-induced hearing loss (NIHL) occurs as a result of long term exposure to workplace noise. The aim of the study was to identify job positions with an increased risk of hearing impairment due to occupational noise exposure, by analyzing changes in audiometric findings over a six-month period of work under conditions with elevated noise levels. The study included participants exposed to workplace noise and participants working in a quiet environment, employed in the same companies but in different job positions. Audiometric examinations were conducted at baseline and after six months of follow-up. Paired and independent-samples t-tests were applied. A statistically significant difference in hearing loss was found among participants exposed to occupational noise during the six-month period (t = 4.84, df = 35, p < 0.001), while no significant difference was observed among participants working in a quiet environment (t = 1.64, df = 35, p = 0.109). A significant difference was also identified between the noise-exposed group and the control group in mean hearing threshold values at baseline and at the final assessment after six months (t = 4.13, df = 71, p < 0.001). Occupations with an increased risk of the development and progression of hearing impairment were identified. The results confirmed the need for continuous monitoring and implementation of preventive hearing protection measures in high-risk workplaces, including oil refineries, textile and metal industries, the wood-processing sector, and selected service industries.